The nitrogen fixing activity of the soybean Glycine max (L.) Merr. near-isogenic by E-genes lines under different photoperiod - Попова, Ю. В.; Жмурко, В. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The effect of short photoperiod (9 hr) on nitrogen-fixing activity of the soybean (Glycine max (L.) Merr.) lines isogenic by E-genes was investigated in the three-year field experiments. It was found that the nitrogenase activity depends on weather conditions, state of E-genes alleles, and changes during ontogeny, but it is the greatest influenced by the photoperiod duration. Nitrogen fixation activity decreased at all isogenic lines under short photoperiod, at other equal conditions. It is assumed that soybean symbiotic nitrogen fixation exposed to photoperiodic control, which is carried out by assimilates flow changing between the apical meristems and root system under the different photoperiod.